2017
DOI: 10.1242/dev.136713
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblast niche position is controlled by PI3-kinase dependent DE-Cadherin adhesion

Abstract: Correct positioning of stem cells within their niche is essential for tissue morphogenesis and homeostasis. How stem cells acquire and maintain niche position remains largely unknown. Here, we show that a subset of brain neuroblasts (NBs) in Drosophila utilize Phosphoinositide 3-kinase (PI3-kinase) and DE-cadherin to build adhesive contact for NB niche positioning. NBs remain within their native microenvironment when levels of PI3-kinase activity and DEcadherin are elevated in NBs. This occurs through PI3-kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 46 publications
(37 reference statements)
1
30
0
Order By: Relevance
“…Primary protrusion of qNSCs directly contacts with neuropil, however, proteins at NSC-neuropil contact sites were previously unknown. Cell adhesion molecule E-cad, abundantly expressed in 3 rd instar larval NSCs, is often localized to cell-cell contacts and was recently reported to localize to MB NSC-cortex glia contact in the adult Drosophila brain (Doyle et al, 2017;Dumstrei et al, 2003). We show, for the first time, that Ecad forms an endfeet-like structure at NSC-neuropil contact sites.…”
Section: Discussionmentioning
confidence: 56%
“…Primary protrusion of qNSCs directly contacts with neuropil, however, proteins at NSC-neuropil contact sites were previously unknown. Cell adhesion molecule E-cad, abundantly expressed in 3 rd instar larval NSCs, is often localized to cell-cell contacts and was recently reported to localize to MB NSC-cortex glia contact in the adult Drosophila brain (Doyle et al, 2017;Dumstrei et al, 2003). We show, for the first time, that Ecad forms an endfeet-like structure at NSC-neuropil contact sites.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies show that extrinsic contact-dependent cues are required to polarize embryonic neuroblasts, which is essential for proper asymmetric cell division (Siegrist and Doe, 2006). DE-cadherin, a contact-dependent cue that is essential for neuroblast proliferation (Doyle et al, 2017;Dumstrei et al, 2003), showed reduced expression in cortex glia upon Pvr loss, and DE-cadherin co-overexpression largely rescued the effects of Pvr knockdown. In the Drosophila germline, DE-cadherin functions in homophilic adhesion between germline stem (GSCs) cells and niche cells, and this anchors GSCs to the niche to promote self-renewal and orient asymmetric cell division (Inaba et al, 2010;Song et al, 2002).…”
Section: Pvf-pvr Signaling and Cortex Glia Development And Functionmentioning
confidence: 92%
“…PI3K signaling is required in neuroblasts to maintain growth and proliferation throughout larval development (Chell and Brand, 2010;Cheng et al, 2011;Sousa-Nunes et al, 2011), and PI3K signaling in neuroblasts is required to anchor neuroblasts in the cortex glia niche through DE-cadherin-dependent adhesion (Doyle et al, 2017). DE-Cadherin is expressed in larval central brain cortex glia and localizes at the interface of cortex glia and central brain neuroblasts, and glial DE-cadherin (DEcad) function is essential for maintenance and proliferation of neuroblasts and their progeny (Dumstrei et al, 2003;Holcroft et al, 2013).…”
Section: Loss Of Glial Pvr Causes Loss Of Pi3k and De-cadherin Signalingmentioning
confidence: 99%
“…After thorough washing in 0.1% Triton-x/PBS, antibody staining was performed according to standard methods (Doyle et al, 2017; Siegrist et al, 2010). Primary antibodies used in this study were: chicken anti-GFP (1:100, Abcam, Cambridge, MA), rat anti-Deadpan (1:100, Abcam), rabbit anti-Scribble (1:200; gift of C. Doe), and rabbit anti-Eyeless (1:1000; gift of U. Waldorf).…”
Section: Methodsmentioning
confidence: 99%